Interaction of microglia with infiltrating immune cells in the different phases of stroke. (2nd November 2020) - Berchtold, Daniel; Priller, Josef; Meisel, Christian; Meisel, Andreas
Abstract: Stroke, in association with its complications, is one of the leading causes of mortality and morbidity worldwide. Cerebral ischemia triggers an inflammatory response in the brain that is controlled by the activation of resident microglia as well as the infiltration of peripheral myeloid and lymphoid cells into the brain parenchyma. This inflammation has been shown to have both beneficial and detrimental effects on stroke outcome. The focus of this review lies on the functions of myeloid cells and their interaction with infiltrating lymphocytes in different phases of stroke. A detailed and time‐specific understanding of the contribution of different immune cell subsets during the course of cerebral ischemia is crucial to specifically promote beneficial and inhibit detrimental effects of inflammation on stroke outcome. Abstract : Stroke is one of the leading causes of mortality and morbidity worldwide. Brain inflammation, mediated by myeloid and lymphoid immune cells, is an inherent component of stroke pathology and contributes to the functional outcome after ischemia.